CINDER & GLASS - De la Cruz, Melissa, 1971- (New York : G.P PUTNAM'S SONS, 2022)
For this princess, winning the crown is no fairytale
"For this princess, winning the crown is no fairytale" -- Cover.
Keywords: Cinderella (Tale) -- Adaptations -- Fiction; Princes -- Fiction; Orphans -- Fiction; Fantasy fiction; Romance fiction